The Status of Educational Research and Policy Analysis in Sub-Saharan Africa - Namuddu, Katherine; Tapsoba, J. M. (IDRC, Ottawa, ON, CA, 1993)
Although building a functional and credible research capacity is a costly enterprise, donor agencies as well as policy makers recognize more and more that if universities in Africa areVto play a positive role in the development process, an effort should be made to build aV"critical mass of professional African analysts" (World Bank 1990a: 1) through investment in human capital and in key institutions, as well as in a mobilization of resources to implement programmes of action. A chief motivating factor is the realization that after two or three decades of development activity, most sub-Saharan African countries, instead of experiencing the expected expansion and consolidation of their educational systems, have suffered a decline since the early years of their independence. Researchers argue that the acuteness of the perception of this decline is related to the faith placed in education as a key to economic development (Wright 1981). In some countries loss of faith in the educational system can be used to explain cuts in budgetary provisions for education in general and higher education in particular. In others such cuts have more to do with general economic decline. Whatever the cause, researchers have suggested that one of the direct consequences of budgetary restrictions has been a decline in research capacity. This, in tum, has marginalized universities in their quest to produce knowledge from research and data that can influence their societies (Kinyanjui 1991).
Keywords: Educational Research; Policy Analysis; Capacity Building